The Latest Developments In HIV Vaccines - I Ketut Agus Somia; Gerry Setiawan (Green Publisher Indonesia, 2024)
Medical knowledge of HIV and AIDS is rapidly evolving, leading to increased understanding of the disease, its immunology, and clinical manifestations. Antiretroviral therapy has provided a means of controlling but not curing the disease. However, new challenges are emerging. A vaccine is one prevention tool that remains elusive. Research over the past 40 years illustrates how difficult it is to induce effective immunity against this virus. Progress of vaccine development has been hindered by the extensive genetic variability of HIV, our limited understanding of immune responses required to protect against HIV acquisition, and funding issues. Since the beginning of HIV vaccine development, it is worth noting that there have been many advances and innovations to make HIV vaccine more effective and safer.